How Single Older Men Reach Poverty and Its Relationship with Help‐Seeking Preferences. (19th March 2021) - Murayama, Yoh; Yamazaki, Sachiko; Hasebe, Masami; Takahashi, Tomoya; Kobayashi, Erika
Abstract: This study aimed to clarify patterns of poverty among single older men and examine this population's help‐seeking preferences. Semi‐structured interviews were conducted with 83 older single men in poverty. Three main patterns of poverty were identified: lifelong, job turnover, and retirement. A common characteristic among these patterns indicated that they did not recognize their difficulties as problems. Furthermore, we identified five groups of help‐receiving preferences: independent, resignation, mutual‐aid, other‐oriented, and seeking. Among these, the independent and resignation groups were influenced by past experiences of failing to seek help, which was characteristic of the lifelong pattern type. Furthermore, the mutual‐aid and seeking groups were oriented toward positive help‐seeking, which was characteristic of the job turnover and retirement pattern types. However, neither group actively sought help for social isolation or lack of social support, suggesting that it would have been challenging to establish social relationships early on in life. Thus, it is important to establish initiatives that enable older people to understand their current state and to think about their future depending on three patterns of poverty.